Pelatihan Local Area Network (LAN) dan Access Point Pada SMK Bina Guna Tanah Jawa Kabupaten Simalungun - Iin Parlina; Muhammad Ridwan Lubis (Universitas Medan Area, 2019)
With the development of current technology that is increasing drastically, so it requires everyone to understand how to install a local area network and how to access points to share data. In this case it is necessary to do training for Vocational students who are actively studying especially for Computer Network Engineering (CNE) majors to improve students' abilities in network installation. Because there are still many students who do not understand about networks. So that this training is very necessary, and the preparation of female students is even more mature in facing the competency exam in the future.